PENEGAKAN HUKUM ADMINISTRASI TERHADAP LIMBAH INDUSTRI FARMASI BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 (CONTOH KASUS: PENCEMARAN LIMBAH PARASETAMOL DI PERAIRAN JAKARTA) - Meidiana Novriyanti; Keyzia Betarli Lengkong; Christopher David Nagaria; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
Waste from the pharmaceutical industry is hazardous waste because it is not only dangerous but also poisonous. If it is not processed and managed properly, it will seriously endanger the environment of the living things around it. Therefore, strict enforcement of the law is required to administer environmental permits for these business activities. Enforcement that violations of environmental management standards can be adjudicated by virtue of Law No. 32 of 2009. The sanction includes administrative, criminal and civil sanctions. Administrative sanctions that the government can impose are government injunctions, revocation of environmental permits to do business, and suspension of those permits. Enforcing regulations in the environmental sector is one of the tasks that PPLH has to carry out, so that companies that have failed to comply with regulations on environmental management, in particular regulations on liquid waste management, are subject to sanction in accordance with applicable regulations. Based on the description above, this study will discuss the enforcement of administrative law against pharmaceutical waste, namely paracetamol in Angke Bay and Ancol Beach waters which are currently being discussed. This research is structured normatively based on secondary data and obtained to be analyzed by qualitative methods and described descriptively.